Evolution of the brightest cluster galaxies: the influence of morphology, stellar mass and environment - Zhao, Dongyao; Aragón-Salamanca, Alfonso; Conselice, Christopher J. (Oxford University Press, 2015)
Using a sample of 425 nearby brightest cluster galaxies (BCGs) from von der Linden et al., we study the relationship between their internal properties (stellar masses, structural parameters and morphologies) and their environment. More massive BCGs tend to inhabit denser regions and more massive clusters than lower mass BCGs. Furthermore, cDs, which are BCGs with particularly extended envelopes, seem to prefer marginally denser regions and tend to be hosted by more massive haloes than elliptical BCGs. cD and elliptical BCGs show parallel positive correlations between their stellar masses and environmental densities. However, at a fixed environmental density, cDs are, on average,∼ 40 per cent more massive. Our results, together with the findings of previous studies, suggest an evolutionary link between elliptical and cD BCGs. We suggest that most present-day cDs started their life as ellipticals, which subsequently grew in stellar mass and size due to mergers. In this process, the cD envelope developed. The large scatter in the stellar masses and sizes of the cDs reflects their different merger histories. The growth of the BCGs in mass and size seems to be linked to the hierarchical growth of the structures they inhabit: as the groups and clusters became denser and more massive, the BCGs at their centres also grew. This process is nearing completion since the majority (∼60 per cent)of the BCGs in the local Universe have cD morphology. However, the presence of galaxies with intermediate morphological classes (between ellipticals and cDs) suggests that the growth and morphological transformation of some BCGs is still ongoing.